Mechanical Properties Analysis of a Monolayer Biphenylene at Different Temperatures - Mohammad Amin Hemmatpour Khotbesara; Masoud Ajri; Majid Samadiyan (مجله مدل سازی در مهندسی)
In this study, the mechanical behavior of the newest allotrope of carbon called biphenylene network (BPN) has been investigated using molecular dynamics simulations. The structure of BPN consists of four, six, and eight-membered carbon rings hybridized with sp2. In this study, the interatomic potential is considered to be AIRBO, and the tensile behavior of this structure has been modeled at different temperatures. After simulation, the Young's modulus and yield stress of biphenylene at different temperatures have been obtained in the armchair direction and zig-zag direction. The Young's modulus in the zig-zag direction at all temperatures is about 14 to 29% higher than the other direction, which indicates the orthotropic behavior of this structure. In addition, with the increase in temperature, the failure strain and Young's modulus have decreased due to the increase in the distance between the atoms and the decrease in energy. It has also been shown that the failure of BPN is brittle. The results of this study show that BPN shares some of the exceptional properties of graphene..